2017
DOI: 10.1007/s12576-017-0583-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal response to anaphylaxis in anesthetized rats and isolated perfused rat kidneys: roles of nitric oxide

Abstract: We determined the renal responses to anaphylaxis and the effects of a nitric oxide synthesis inhibitor, L-NAME, in anesthetized rats and isolated perfused rat kidneys. After the ovalbumin antigen injection, the sensitized rats showed transient and substantial decreases in mean blood pressure and renal blood flow and an increase in renal vascular resistance. Creatinine clearance, a measure of renal function, decreased to 53% baseline at 2 h after antigen. L-NAME pretreatment significantly enhanced the antigen-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Excitation of efferent sympathetic nerves causes vasoconstriction in the innervated vascular beds and a consequent reduction in the relevant blood flow. Consistently, in kidney and skeletal muscle, renal and lumbar sympathoexcitation (24,25) was observed in accord with increases in renal and femoral vascular resistance, respectively, along with reductions in renal and femoral blood flow during anaphylactic hypotension (16,25). However, in this study, the antigen-induced increase in ef-GSNA we observed was not associated with an increased gastric vascular resistance, as previously observed in the same rat anaphylaxis model (12): ef-GSNA increased at the early phase (1-10 min after ovalbumin antigen injection), whereas the gastric vascular resistance increased at the late phase, 9 -40 min after antigen injection in the present study ( Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Excitation of efferent sympathetic nerves causes vasoconstriction in the innervated vascular beds and a consequent reduction in the relevant blood flow. Consistently, in kidney and skeletal muscle, renal and lumbar sympathoexcitation (24,25) was observed in accord with increases in renal and femoral vascular resistance, respectively, along with reductions in renal and femoral blood flow during anaphylactic hypotension (16,25). However, in this study, the antigen-induced increase in ef-GSNA we observed was not associated with an increased gastric vascular resistance, as previously observed in the same rat anaphylaxis model (12): ef-GSNA increased at the early phase (1-10 min after ovalbumin antigen injection), whereas the gastric vascular resistance increased at the late phase, 9 -40 min after antigen injection in the present study ( Fig.…”
Section: Discussionmentioning
confidence: 53%
“…When the abdomen was opened, the kidneys were revealed. The artery and vein of the left kidney were separated and renal blood flow (RBF) was measured for 30 min using a flow meter equipped with a special probe (T402, America) and blood flow was recorded as a chart [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…13,14 The rats were anesthetized and a longitudinal cut was created in the abdomen with a blade. After separation of the artery and vein of the left kidney, after stabilization of amount of blood flow, the renal blood flow (RBF) was recorded for 30 min by using flow meter of Power Lab instrument (T402, America) 15,16 and the mean of blood flow was measured for 30 min. The blood sample was taken from the abdominal aorta by syringe of cold heparin.…”
Section: Methodsmentioning
confidence: 99%